Building construction completion delays: factors and effects / Muhammad Tarmizi Abd Rashid and Sr. Dr. Nor Suzila Lop - Abd Rashid, Muhammad Tarmizi; Lop, Nor Suzila (2020)
Investing to the construction project does not promise a profit to the clients. The project can be delay or worse, which is abandonment. Each client want their project going well so they can meet their objectives. Therefore, this research aim to minimize the delay of building construction completion in Malaysia. The objectives of this research are (i) To identify the factors affecting delays of building construction completion in Malaysia (ii) To determine the effects of building construction completion delays to the clients, consultants and contractors (iii) To suggest action that could minimize building construction delays. In order to achieve the objectives, 90 questionnaires were distributed to the project clients, contractors, and construction consultant. Clients often change order during construction phase frequently is the main factor affecting delays, clients delay getting profit from the development as the main effect of delays and clients should ease the interim payment and do it on time as the main steps to minimize delays.